2021
DOI: 10.3390/diagnostics11122172
|View full text |Cite
|
Sign up to set email alerts
|

INSM1, a Novel Biomarker for Detection of Neuroendocrine Neoplasms: Cytopathologists’ View

Abstract: Background: Insulinoma-associated protein 1 (INSM1) has been considered as a novel immunostain for neuroendocrine tumors (NETs) and is hypothesized to be more reliable than first-generation NET biomarkers, such as CGA (chromogranin A), SYP (synaptophysin) and CD56 (neural cell adhesion molecule). In this review, we summarize existing literature on INSM1′s reliability as an immunostain for detection of various NETs, its results in comparison to first-generation NET biomarkers, and its expression in both non-NET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 79 publications
2
25
0
Order By: Relevance
“…Multiple immune-histochemical studies demonstrated that the detection of INSM1 expression is a super sensitive and specific diagnostic biomarker in NETs as compared with conventional NE markers (CGA, SYP, and CD56) [ 54 , 55 ]. Functional studies of INSM1 in NETs revealed that INSM1 exhibited regulatory roles in the cellular signaling axis critical for cell growth and oncogenesis including NB [ 3 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple immune-histochemical studies demonstrated that the detection of INSM1 expression is a super sensitive and specific diagnostic biomarker in NETs as compared with conventional NE markers (CGA, SYP, and CD56) [ 54 , 55 ]. Functional studies of INSM1 in NETs revealed that INSM1 exhibited regulatory roles in the cellular signaling axis critical for cell growth and oncogenesis including NB [ 3 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, INSM1 has emerged in clinical practice as a sensitive and specific diagnostic biomarker in NE tumors (NETs). This novel biomarker provides pathologists a useful tool to distinguish NETs from non-NETs, and it represents a more sensitive NE marker as compared to the traditional markers, such as synaptophysin, chromogranin A, and CD56 [ 54 ]. INSM-1 nuclear expression in cytology specimens successfully shows that it is a robust NE marker.…”
Section: Introductionmentioning
confidence: 99%
“…However, use of morphology alone is challenging in tumor specimens from patients who have been treated with agents such as ADT or ARSIs that may alter cellular morphology and give a false impression of the phenotype of a tumor. Another approach is to use immunohistochemistry for canonical NEPC markers, including CHGA, SYP, NSE, CD56 (NCAM1), or INSM1 that are highly expressed in de novo NEPC (114)(115)(116). However, many t-NEPC tumors do not have high expression of these genes, presumably because they are not as far along the continuum of NEPC differentiation as a de novo NEPC tumor (26).…”
Section: Identifying Nepc Tumorsmentioning
confidence: 99%
“…This kind of study has essential output on patient management and quality of treatment. Another marker covered in the Special Issue is a new neuroendocrine biomarker insulinoma-associated protein 1 (INSM1) [ 10 ]. The nuclear expression of INSM1 is practical in all kinds of cytological preparations.…”
mentioning
confidence: 99%
“…The nuclear expression of INSM1 is practical in all kinds of cytological preparations. The review by Maleki et al concluded that INSM1 is a reliable sensitive and specific neuroendocrine marker in various localizations [ 10 ].…”
mentioning
confidence: 99%